2002
DOI: 10.7326/0003-4819-137-7-200210010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction and Renal Dysfunction: A High-Risk Combination

Abstract: Patients with renal failure are at increased risk for death after acute MI and receive less aggressive treatment than patients with normal renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
355
3
15

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(399 citation statements)
references
References 17 publications
26
355
3
15
Order By: Relevance
“…For CV mortality, all-cause mortality, and heart failure-related hospitalization, the risk reduction was greater for subjects with reduced kidney function. 8 Wright et al 6 reported a reduced risk of in-hospital death if patients were treated (nonrandomized) with ACE inhibitors; however, the authors indicated that the use of ACE inhibitors during index hospitalization was lower in patients with CKD. Data from the Cooperative Cardiovascular Project, which included older patients with MI, showed that ACE inhibitors were used more frequently in patients with CKD than in patients with no renal insufficiency and were associated with enhanced survival.…”
Section: ϫ2mentioning
confidence: 97%
“…For CV mortality, all-cause mortality, and heart failure-related hospitalization, the risk reduction was greater for subjects with reduced kidney function. 8 Wright et al 6 reported a reduced risk of in-hospital death if patients were treated (nonrandomized) with ACE inhibitors; however, the authors indicated that the use of ACE inhibitors during index hospitalization was lower in patients with CKD. Data from the Cooperative Cardiovascular Project, which included older patients with MI, showed that ACE inhibitors were used more frequently in patients with CKD than in patients with no renal insufficiency and were associated with enhanced survival.…”
Section: ϫ2mentioning
confidence: 97%
“…Moreover, although ␤-adrenergic blockers and ACE inhibitors improve survival in patients after AMI, 37 these agents are often underused in patients with RI compared with those with normal renal function. 4,38,39 All attempts must be made to prevent contrast nephropathy, including adequate hydration, 40 minimizing contrast use, 29 use of low-osmolar contrast, 41 and possibly administration of N-acetylcysteine. 42 Patients with baseline RI warrant close surveillance and intensive medical management, including tight control of diabetes, hypertension, and dyslipidemia 20 ; dietary modification; and potentially frequent stress testing for early recognition of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, several studies have shown that CKD patients, with documented CHD, do not receive optimal treatment with aspirin, beta-blockers, ACE inhibitors, statins etc. [31,32]. Similarly, patients with CVD do not always receive optimal preventive therapy [33].…”
Section: Discussionmentioning
confidence: 99%